AGE-RELATED PROBLEMS IN CHILDREN IN PRIMARY EDUCATION AND THE IMPORTANCE OF THE PEDAGOGUE IN THEIR PRACTICAL ELIMINATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Age-related problems are one of the most complex events in the voluntary sphere of a child's life should be considered. In the article, there are various problems that children of primary school age have specific features of its manifestation are discussed.